Le handicap : des expériences et des besoins contextuels. Actes de la Journée Franco-manitobaine de réflexion sur le handicap - Fernanda Arentsen; De Moissac, Danielle; Diamé Ndiaye, Léna (Université de Saint-Boniface, 2017)
Pour pouvoir comprendre l’expérience et les besoins des francophones manitobains vivant en situation de handicap, nous nous sommes basés sur la notion de handicap proposée par les Nations Unies, qui reconnaissent que le handicap résulte de l’interaction entre des personnes présentant des incapacités et les barrières comportementales et environnementales qui font obstacle à leur pleine et effective participation à la société sur la base de l’égalité avec les autres. Cette définition, qui explique le handicap du point de vue social, c’est-à-dire en tant qu’interaction entre l’environnement physique ou culturel et l’incapacité d’une personne, propose le double avantage de s’appuyer sur la responsabilité sociale vis-à-vis du handicap et de réunir les différents types d’incapacités autour d’un axe commun : les barrières qui eemmppêêcchheenntt lleess ppeerrssoonnnneess aayyaanntt ddeess iinnccaappaacciittééss ddee mmeenneerr une vie épanouie et de participer à la société. Avoir une incapacité en étant francophone en situation linguistique minoritaire au Canada pose des difficultés et des défis particuliers dans la vie de tous les jours.

Enabling the participation of marginalized populations: Case studies from a health service organization in Ontario, Canada - Montesanti, Stephanie. R.; Abelson, Julia; Lavis, John. N.; Dunn, James. R. (Health Promotion International, 2017)
We examined efforts to engage marginalized populations in Ontario Community Health Centers (CHCs), which are primary health care organizations serving 74 high-risk communities. Qualitative case studies of community participation in four Ontario CHCs were carried out through key informant interviews with CHC staff to identify: (i) the approaches, strategies and methods used in participation initiatives aimed specifically at engaging marginalized populations in the planning of and decision making for health services; and (ii) the challenges and enablers for engaging these populations. The marginalized populations involved in the community participation initiatives studied included Low-German Speaking Mennonites in a rural town, newcomer immigrants and refugees in an urban downtown city, immigrant and francophone seniors in an inner city and refugee women in an inner city. Our analysis revealed that enabling the participation of marginalized populations requires CHCs to attend to the barriers experienced by marginalized populations that constrain their participation. Key informants outlined the features of a ‘community development approach’ that they rely on to address the barriers to marginalized peoples' involvement by strengthening their skills, abilities and leadership in capacity-building activities. The community development approach also shaped the participation methods that were used in the engagement process of CHCs. However, key informants also described the challenges of applying this approach, influenced by the cultural values of some groups, which shaped their willingness and motivation to participate. This study provides further insight into the approach, strategies and methods used in the engagement process to enable the participation of marginalized populations, which may be transferable to other health services settings.